Carbon and nitrogen isotopic composition of particulate organic matter in the Pearl River Estuary and the adjacent shelf. (5th November 2020) - Huang, Chao; Chen, Fajin; Zhang, Shuwen; Chen, Chunqing; Meng, Yafei; Zhu, Qingmei; Song, Zhiguang
Abstract: The isotopic composition (δ 13 C and δ 15 N), organic carbon and nitrogen contents and C/N ratios of suspended particulate organic matter (POM) collected from the Pearl River Estuary and the adjacent shelf during spring and summer of 2017 were determined to understand the main controlling factors of spatiotemporal distribution and to elucidate the sources of particulate organic matter. Our study revealed considerable spatial variability of these parameters. In summer, δ 13 C in the Pearl River Estuary generally increased seawards, reflecting the increasing contribution of marine organic matter. Domestic sewage and industrial wastewater were responsible for relatively high δ 15 N in the Pearl River Estuary. In spring, δ 13 C on the adjacent shelf generally decreased from land to sea, with elevated δ 13 C occurred at the nearshore stations, suggesting that the eutrophic level, phytoplankton biomass and microbial activity played an important role in determining the sources of POM. Compared with δ 13 C, δ 15 N values displayed a complicated spatial distribution. Especially in the bottom water, enriched δ 15 N would be influenced by the degradation and mineralization of suspended matter. Given that isotopic values in summer can be applied in source apportionment, a Bayesian isotope mixing model was used to estimate that in summer the marine and terrestrial organic matter contributed 47% and 38% in the Pearl River Estuary, respectively. The greatest contribution from marine-derived POM (73%) was observed on the adjacent shelf. Highlights: A seaward increase of δ 13 C in the Pearl River Estuary indicates the increasing contribution of marine organic matter. Enriched δ 13 C of the nearshore areas reflect the influence of eutrophic level, phytoplankton biomass and microbial activity. Higher δ 15 N in the Pearl River Estuary can be mainly attributed to 15 N-enriched contaminants.